2021
DOI: 10.21608/edj.2021.50959.1360
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Technique Sensitivity and Gingival Health in Management of Cervical Lesions Performed Using Subgingival Clamp Versus Retraction Cord: A Randomized Controlled Clinical Trial

Abstract: Aim: the current study was conducted to compare technique sensitivity and gingival health of carious and non-carious cervical lesions performed using subgingival clamps and retraction cords.Methodology: 24 teeth with carious or non-carious cervical lesions were divided randomly into 2 groups receiving one of the two gingival retraction techniques, either subgingival clamp (KSK clamp #44) or retraction cord (Ultrapak E), technique sensitivity was evaluated at baseline (before application) and immediately after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…The time required for retraction cord placement was statistically significant compared to the rubber dam application. The results of my study were incomparable with other studies (Loguercio et al, 2015;Shehab Eldin et al, 2021) in which the time difference was insignificant. However, It is commonly seen that rubber dam is considered time-consuming, challenging to use, and cumbersome to apply (Joshi et al, 2023;Jurado et al, 2021).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The time required for retraction cord placement was statistically significant compared to the rubber dam application. The results of my study were incomparable with other studies (Loguercio et al, 2015;Shehab Eldin et al, 2021) in which the time difference was insignificant. However, It is commonly seen that rubber dam is considered time-consuming, challenging to use, and cumbersome to apply (Joshi et al, 2023;Jurado et al, 2021).…”
Section: Discussioncontrasting
confidence: 99%
“…These findings align with my study, in which more patients asked for anesthesia while a retraction cord was placed. My study's results contradicted those found in studies (Loguercio et al, 2015;Shehab Eldin et al, 2021), where an almost equal number of participants from both groups asked for anesthesia. This study concluded that gingival bleeding was observed immediately after the procedure in both groups, but the difference was insignificant.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations